Pengaruh Disiplin Kerja Dan Kemampuan Kerja Terhadap Kinerja Aparatur Desa di Kecamatan Nita Kabupaten Sikka (Studi Kasus Pada Desa Nita, Desa Nitakloang, Desa Tebuk dan Desa Lusitada) - Emelinda Lopi Kedang; Walter Obon; Margaretha Yilianti (Lembaga Pengembangan Kinerja Dosen, 2023)
The background of this research was village administration performance in Nita Sub-district had not been maximized. This research aimed to (1) determine the description of administration performance, work discipline, and workability in the villages of Nita Sub- district; and (2) analyze the effect of work discipline and workability on the village administration performance in Nita Sub-district both partially and simultaneously. The population in this research was village administration as many as 36 people. This research was conducted by census or saturated sampling due to limited population. Data were collected through questionnaires and analysed through desctiptive and inferential statistical methods, namely multiple linear regression. The hypothesis testing was done through the F- test and t-test. The results of descriptive analysis showed that the variables of village administration performance, work discipline, and workability were categorized as good. The statistical results of the t- test showed that partially the work discipline and workability variables had a positive and significant effect on village administration performance. The result of the F-test significan effect on employee performance. The results of the deretmination analysis indicated that the two independen variables in this research could explain the fluctuation of employee performance by 38, 8%.